2014
DOI: 10.1007/s00442-014-3088-2
|View full text |Cite
|
Sign up to set email alerts
|

Human alteration of natural light cycles: causes and ecological consequences

Abstract: Artificial light at night is profoundly altering natural light cycles, particularly as perceived by many organisms, over extensive areas of the globe. This alteration comprises the introduction of light at night at places and times at which it has not previously occurred, and with different spectral signatures. Given the long geological periods for which light cycles have previously been consistent, this constitutes a novel environmental pressure, and one for which there is evidence for biological effects that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
215
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(220 citation statements)
references
References 143 publications
(165 reference statements)
2
215
0
3
Order By: Relevance
“…Given the nature of such images, it is challenging to use these to make some categorical quantification of the extent of ALAN, although it is plainly much more widespread than urban infrastructure alone, mainly because of the skyglow effect. One estimate that accounted explicitly for the effects of skyglow was that 18.7% of the global land area experienced ALAN [12], another based more directly on satellite imagery that 11.4% of terrestrial and 0.2% of marine areas of the globe experienced ALAN [11], and another that ALAN is increasing at around 6% per annum with huge geographical variation (0-20%; [14]). …”
Section: The Challengementioning
confidence: 99%
See 2 more Smart Citations
“…Given the nature of such images, it is challenging to use these to make some categorical quantification of the extent of ALAN, although it is plainly much more widespread than urban infrastructure alone, mainly because of the skyglow effect. One estimate that accounted explicitly for the effects of skyglow was that 18.7% of the global land area experienced ALAN [12], another based more directly on satellite imagery that 11.4% of terrestrial and 0.2% of marine areas of the globe experienced ALAN [11], and another that ALAN is increasing at around 6% per annum with huge geographical variation (0-20%; [14]). …”
Section: The Challengementioning
confidence: 99%
“…Second, ALAN is introducing light with a spectrum that is different from those of sunlight, moonlight or starlight [11]. The spectrum of ALAN depends fundamentally on the kind of lighting device that is being used, ranging from narrow (e.g.…”
Section: The Challengementioning
confidence: 99%
See 1 more Smart Citation
“…Directly, it represents a threat to biodiversity [4] and can alter species distribution, community structure, and, possibly, ecosystem functions and processes [5]. Indirectly, light pollution has strong synergies and interactions with other pressures on biodiversity, including habitat fragmentation and climate change [6].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the recent advances in this field a growing body of research has revealed the accelerated pace at which light pollution is affecting different aspects of our lives. Light pollution -the alteration of the natural levels of nighttime darkness due to artificial lighting-shows an increasing trend and its farreaching consequences have been reported in such diverse fields as basic science [1][2][3] , energy management [4][5][6][7] , ecology [8][9][10][11] and human health [12][13][14][15][16] , to mention a few.…”
Section: Introductionmentioning
confidence: 99%